Lessons Learned From "A Day for Youth Voices on the Opioid Overdose Crisis" and Future Directions for Research on the Youth Polysubstance Use Emergency in Canada. (June 2022) - Nairn, Stephanie A.; Isaacs, Jason Y.; Stewart, Sherry H.; Hawke, Lisa D.; Thulien, Madison; Fast, Danya; Knight, Rod; Conrod, Patricia; Henderson, Joanna; Khan, Faria; Lam, Alice; Haines-Saah, Rebecca J.
ABSTRACT: Objectives: There is a lack of knowledge regarding how diverse young people (ages 15–25) experience opioid use, connect to opioid-related services, and navigate opioid use disorder. Knowledge is urgently needed to inform the development of prevention and treatment for youth. This article outlines a protocol for a pan-Canadian youth engagement summit and discusses the successes and challenges experienced and outlines suggestions for future engagement initiatives of this kind. Methods: The challenges and successes we present are premised on the results of a survey based on the Public and Patient Engagement Evaluation Tool administered to participating youth that consisted of closed-ended and open-ended questions and demographic data, as well as from feedback provided informally to the summit teams and team members' reflections. Results: About 169 youth participated in the summit and represented diverse youth populations from 6 different provinces with varied experiences with opioid use. The majority of participants were women. N = 126 youth completed a feedback questionnaire. Most of the youth rated the event highly. Most youth felt they were able to express their views, that their views were heard, that a broad range of topics were discussed, and a broad range of viewpoints were represented. Most youth felt the event was a good use of their time and were satisfied. Youth were less confident that the summit would impact governmental policies and would be used by relevant stakeholders, including service providers. Summit successes included engagement, the provision of education/information and psychological support, normalization, and validation. Summit challenges related to time and timing of the event, content, and interaction(s). Conclusion: Our summit represented a unique pastiche of youth participation and engagement modalities. Going forward, we suggest that researchers and summit planners ensure youth are engaged in earlier stages of planning, that the content be responsive to a spectrum of youth knowledge about opioids (within site), incorporate flexibility with the formats of interaction, as well as potentially include other stakeholders to improve youth confidence that their feedback will have impacts beyond the summit activity. Abstract : Objectifs: On accuse un manque de données pour comprendre la diversité des expériences relatives à l'usage d'opioïdes chez les jeunes de 15 à 25 ans, leur rapport aux services offerts et la façon dont ils composent avec leur usage d'opioïdes. Il est urgent d'obtenir de telles données pour élaborer des plans de prévention et de traitement pour les jeunes. Cet article propose un protocole pour la tenue d'un sommet pancanadien sur l'engagement des jeunes, aborde les réussites et les défis vécus et suggère d'autres projets d'engagement du même type. Méthodologie: Les défis et les réussites présentés reposent sur les résultats d'un sondage fondé sur la Boîte à outil d'évaluation de l'engagement des patients et du public, à laquelle ont été soumis les jeunes participants et qui était constituée d'un ensemble de questions fermées et ouvertes et de données démographiques, de même que sur les commentaires informels fournis aux équipes du sommet et les réflexions des membres de l'équipe. Résultats: Lors du sommet, 169 jeunes participants représentant diverses populations de 6 provinces aux expériences variées quant à l'usage d'opioïdes étaient présents. La majorité des participants étaient des femmes. Parmi eux, 126 jeunes ont rempli le questionnaire de rétroaction. La plupart des jeunes ont évalué le sommet positivement. La plupart ont senti qu'ils pouvaient exprimer leurs points de vue, que leur opinion était écoutée, qu'une grande variété de sujets ont été abordés, et qu'une grande diversité de points de vue étaient représentés. La plupart des jeunes étaient d'avis qu'il s'agissait d'un bon usage de leur temps et étaient satisfaits de l'événement. Les répondants avaient peu d'espoir que le sommet ait des retombées sur les politiques gouvernementales et qu'il soit utile aux intervenants tels que les fournisseurs de soins. Le sommet a été une réussite sur les plans de la participation, des renseignements et du soutien psychologique fournis, de la normalisation et de la validation. Le sommet pourrait être amélioré en ce qui concerne le moment et l'horaire de l'événement, son contenu et les interactions. Conclusion: Notre sommet a représenté un mélange unique de participation des jeunes et de modalités d'engagement. À l'avenir, nous suggérons que les chercheurs et les organisateurs du sommet assurent l'engagement des jeunes plus tôt dans le processus d'organisation, que le contenu soit adapté à l'éventail de connaissances des jeunes sur les opioïdes, qu'il y ait une flexibilité quant au format des interactions et que d'autre intervenants soient potentiellement inclus pour que les jeunes sentent que leurs commentaires auront une portée au-delà de l'événement.